Diagnosis and treatment of biliary complications of hydatidosis - Marella, Muzio S (Cirugía del Uruguay, 1973)
All cases of hepatic hydatidosis are related to the biliary tract and appear in two forms: a) cystobiliary communication or fisurisation and b) open, evacuated or fistulized cyst . of biliary tract. Two surgical situations arise, according to the degree of biliary involvement: A) In the case. of communicated or fisurized cyst, it becomes necessary to evacuate the parasite and drain the cavity; B) In open, evacuated or fistulized cysts, three surgical procedures are applicable: i) Cystostomy;. which is the fundamental operation. ii) Cystostomy and drainage of biliary tract:' this is the complete surgical procedure. iii) Choledochostomy. This procedure is generally incomplete as sole conduct, but it may also be complementary to prior cystostomy. Experience is documented by the two statistics on which this paper is based.